Assessment of Management Effectiveness of Protected Areas for Sustainable Development (Case Study: Dez, Shimbar, Koraii) - Fakhrieh Mohseni; Gholam Reza Sabzghabaei; Soolmaz Dashti (جغرافیا و پایداری محیط)
Protected areas are one of the most important and most effective instruments in the world that have been established to protect biodiversity. In recent decades, due to the rapid growth of human population growth and the destruction of natural resources the global methods of protected areas management effectiveness have been widely used for sustainable development. The use of international methods in the management of protected areas will achieve sustainable development along with the maximum protection of biodiversity; therefore, the methods have been developed to assess the effectiveness of management of protected areas. Khuzestan Province, with its high values, both in the water sector and in the land and coastal areas, has provided the basis for the establishment of a suitable substrate for biodiversity in the protected areas of the province. In this study, the assessment of the management effectiveness of Dez, Shimbar and Koraii protected areas with different climatic characteristics and management experience over 5 years has been reviewed. The RAPPAM methodology was used to assess and explain the capacity of Khuzestan and to ensure the sustainable development. This method, as a decision tool for promoting effective management to achieve management goals, has four main indicators of Inputs, Outputs, Design and Planning and Processes.The results show that Dez protected area with 128 score has the highest management effectiveness score and Shimbar with 64 score has the lowest management effectiveness score in the studied areas; This indicates that protected areas like Shimbar with the lower Management experience need more attention and a better management solution from their respective organizations. Extended Abstract 1-Introduction Protected areas are one of the most important and effective tools in the world that have been established to protect biodiversity.The view of environmental management based on natural resources management states that human needs of natural resources and the use of these resources over many years should be possible (Ghaffari et al., 1995: 86). Therefore, management and effectiveness assessment are key factors for long-term sustainability of protected areas (Joppa et al., 2013; 1).The international conservation community has been sensitive to the effectiveness of protected areas at least two decades ago (Hockings et al., 2006). In recent years, many countries and conservation organizations have developed a variety of methods to assess the effectiveness of protected areas (Hochkings, 2010: 1). More than 50 different tools were used to assess the management effectiveness in protected areas in more than 100 countries (Leverington et al., 2010: 687). Despite the wide range of quick assessment methods, these methods are used less in our country to assess the effectiveness of management of protected areas. Khuzestan Province has a set of ecological, biological and eventually environmental values, both in the water sector and in the land and coastal areas, provided the basis for creating a suitable biodiversity enrichment base (Nabavi et al., 2010: 149). These areas, which have undergone many changes in recent years, require more attention and management studies. 2-Materials and Methods The methodology of rapid assessment and prioritization of Protected Area Management (RAPPAM) is based on the process of a set of questionnaires. Analysis of the effectiveness of methodological management has four pillars (indicators) that affect the management of the area including planning, inputs, processes, and Outputs, each of which consists of several parts. All sectors except management have a separate questionnaire for assessing the region. First, using the archival documents and information of the protected areas, in order to determine the statistical society, the status of the forces employed in the protected areas of the province was examined. Since surveys and participation in working groups were not possible for all members of the statistical community, according to the Kerjcie and Morgan formula (1970), the number of samples required for the survey was determined. Questionnaire responses and the way to rate regional design and planning questionnaires, inputs, management decision making processes, and management outputs were organized as 4 options with zero points, more with 1 point, more yes with 2 points and yes with 3 points (WWF.2003). The analysis of the management effectiveness for a single site can determine the strengths and weaknesses of a region if the comparative analysis of a large number of regions (by determining the average scores of each question) can identify the weaknesses and strengths of the system. The result of the analysis of the effectiveness of access management is from 0 to 300 points. Managers of protected areas and policymakers can use this information to regulate regional policies, allocate credits, and develop technical support programs (WWF 2003). 3-Results and Discussion The results of studies based on RAPPAM methodology in Figure 1 show that planning has the highest score among the indicators of management effectiveness. This index (planning) has the highest score in Rhapsody in Russia (Tyrlyshkin et al., 2003; 17), Turkey (Kurdoğlu and Çokçaliskan, 2011: 17219), China and Taiwan (Lu et al, 2012: 278). This indicates the existence of proper planning in studied protected areas as compared to other indicators affecting the management effectiveness. Management Outputs data in the present study has the least effect and score among management effectiveness indicators. The Dez protected area ​​ has the highest score in the inputs index. The Koraii protected area with the highest score in the management process index and in the management decision-making segment reflects the shared management and staffing of the communities with local communities and effective communication among management, employees and local communities. The weakest outputs of infrastructure development in the regions is as a management outputs, while the output in China (Li, 2003: 13) is known as the strongest outflow.